Lack of Outer Membrane Protein A Enhances the Release of Outer Membrane Vesicles and Survival of Vibrio cholerae and Suppresses Viability of Acanthamoeba castellanii - Soni Priya Valeru; Salah Shanan; Haifa Alossimi; Amir Saeed; Gunnar Sandström; Hadi Abd (International Journal of Microbiology)
Vibrio cholerae, the causative agent of the diarrhoeal disease cholera, survives in aquatic environments. The bacterium has developed a survival strategy to grow and survive inside Acanthamoeba castellanii. It has been shown that V. cholerae expresses outer membrane proteins as virulence factors playing a role in the adherence to interacted host cells. This study examined the role of outer membrane protein A (OmpA) and outer membrane vesicles (OMVs) in survival of V. cholerae alone and during its interaction with A. castellanii. The results showed that an OmpA mutant of V. cholerae survived longer than wild-type V. cholerae when cultivated alone. Cocultivation with A. castellanii enhanced the survival of both bacterial strains and OmpA protein exhibited no effect on attachment, engulfment, and survival inside the amoebae. However, cocultivation of the OmpA mutant of V. cholerae decreased the viability of A. castellanii and this bacterial strain released more OMVs than wild-type V. cholerae. Surprisingly, treatment of amoeba cells with OMVs isolated from the OmpA mutant significantly decreased viable counts of the amoeba cells. In conclusion, the results might highlight a regulating rule for OmpA in survival of V. cholerae and OMVs as a potent virulence factor for this bacterium towards eukaryotes in the environment.